Напряженное состояние упругого тела с двумя соосными круговыми трещинами нормального отрыва при действии начальных напряжений - Богданов, В.Л. (Видавничий дім "Академперіодика" НАН України, 2008)
An axisymmetric problem on the interaction of two parallel coaxial cracks of normal rupture in an infinite material with initial stresses acting along cracks is investigated with the use of approaches of the three-dimensional linearized mechanics of solids. Numerical results are obtained for a highly elastic material with the Bartenev–Khazanovich elastic potential. The dependence of the stress intensity factors on the initial stresses, physical-mechanical characteristics of the materials, and geometrical parameters of the problem is analyzed.